Analysis the Effect of Different Surface Preparation Methods on Corrosion Resistance and Adhesion Strength of ASTM A36 Steel Substrate with Surface Tolerant Epoxy Paint as Coating Material - Wijaya, Irwan; Aqila, Daffa; Riastuti, Rini; Ramadhani, Rizal T (Journal of Engineering and Scientific Research, 2024)
In the industrial world, to extend the service life of materials, protection methods are carried out to slow down the material's corrosion rate. The protection method that is often used is the coating method. The coating method is a protection method by coating the substrate material using a coating material to prevent contact between the substrate material and the environment. In this research, the substrate material used is ASTM A36 steel and the coating material used is Surface Tolerant Epoxy paint. The independent variable used in this study lies in the surface preparation method which consists of: solvent cleaning, hand tool cleaning, power tool cleaning, power tool to bare metal cleaning, and abrasive blast cleaning. Different preparation methods result in different roughness and cleanliness of the surface. This can affect changes in the mechanical properties of the coating material, such as corrosion resistance and adhesion strength. Based on the corrosion resistance test, it is found that the abrasive blast cleaning and power tool to bare metal cleaning methods produce the highest corrosion resistance properties because both have a rating number of 8 in the salt spray test results. Based on the adhesion strength test, it is found that the abrasive blast cleaning method also produces the highest adhesion strength. This conclusion refers to the results of the tape x-cut test where the sample produces a rating number 5A where the sample does not experience peeling after testing. In addition, the abrasive blast cleaning method produced the highest adhesion strength in the pull-off test, which was 7.16 Mpa. Thus, the abrasive blast cleaning method is the most effective surface preparation method for ASTM A36 steel before being coated with the coating material. In addition, it can also be concluded that the higher the surface roughness of the sample, the better the corrosion resistance and adhesion strength.